2000
DOI: 10.2337/diabetes.49.11.1840
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced [Ca2+]i abnormalities in human pancreatic islets: important role of overstimulation.

Abstract: Chronic hyperglycemia desensitizes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
46
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 54 publications
(49 reference statements)
10
46
0
2
Order By: Relevance
“…3c, d). Human islets cultured under highglucose conditions for 48 h have previously been described to be desensitised due to increased basal Ca 2+ levels and diminished slow [Ca 2+ ] i oscillations, and thus to respond poorly to glucose stimulation [49]. Interestingly, after 24 h we also found diminished Ca 2+ oscillations but hypersensitisation rather than desensitisation (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…3c, d). Human islets cultured under highglucose conditions for 48 h have previously been described to be desensitised due to increased basal Ca 2+ levels and diminished slow [Ca 2+ ] i oscillations, and thus to respond poorly to glucose stimulation [49]. Interestingly, after 24 h we also found diminished Ca 2+ oscillations but hypersensitisation rather than desensitisation (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…As to possible mechanisms for such an effect, one should consider the possibility of "Ca 2+ toxicity," i.e., negative effects of continuous inflow of Ca 2+ that may activate Ca 2+ -dependent intracellular proteases, thereby triggering apoptosis (20,21). Such a notion would be in line with our findings that culture of human islets for 48 h at high glucose leads to persistent elevation of cytoplasmic Ca 2+ and that diazoxide partly restores the Ca 2+ levels (11).…”
supporting
confidence: 55%
“…As further support, we found that culturing human islets for 48 h at a high glucose concentration completely desensitizes glucose-induced insulin secretion and that this is accompanied by profound alterations in Ca 2+ fluxes (11). Prominent abnormalities were 1) absence of a Ca 2+ response to glucose, 2) doubling of the postculture "resting" level of cyto-plasmic Ca 2+ , and 3) reduction of slow (0.2-0.5 min) Ca 2+ oscillations.…”
supporting
confidence: 53%
“…The enhanced release of [Ca 2+ ] i , possibly during ER stress induction, can increase basal secretion of insulin, but reduce GSIS. Since the enhanced basal [Ca 2+ ] i levels and the reduction of glucose-stimulated Ca 2+ influx was a typical characteristic of islet beta cells isolated from type 2 diabetic patients and since loss of GSIS was associated with enhanced basal [Ca 2+ ] i levels [35], the increase of basal [Ca 2+ ] i levels during ER stress may explain the role of ER stress in GSIS-inhibition in type 2 diabetes. Furthermore, stress kinase JNK, which was activated during the ER stress response may affect insulin secretion since JNK is known to suppress insulin biosynthesis [36].…”
Section: Discussionmentioning
confidence: 99%